Cost-Effectiveness Analysis of Anticholinergics vs. Botox for Urgency Urinary Incontinence: Results from the ABC Randomized Trial - Visco, Anthony G. (Female Pelvic Med Reconstr Surg, 2016)
OBJECTIVES: To compare the cost-effectiveness of Botox and anticholinergic (AC) medications for the management of urgency urinary incontinence (UUI). METHODS: Cost and effectiveness data were analyzed from participants in the Anticholinergic versus Botox Comparison (ABC) randomized trial of daily AC medication versus 100U intradetrusor Botox injection. Societal costs included treatment costs, patient costs, and medical and non-medical utilization during the 6-month trial. Quality-adjusted life-years (QALYs) were calculated based on questionnaire-derived utility measures and annualized based on data collected at baseline through 6 months. We also estimated average direct costs for each treatment through 9 months, the duration of time when approximately half the Botox participants maintained adequate symptom control. RESULTS: Data were analyzed on the 231 women that completed 6-month follow-up in the ABC trial (119 AC and 112 Botox). The mean reduction in UUI episodes/day was not significantly different per group. The cumulative mean direct costs over the first 6 months were also similar, $1,339 for the AC group and $1,266 for the Botox group with AC costs exceeding Botox costs after 5 months. Both groups had considerable QALY gains. Annualizing the 6-month trial results to a 12-month measure, the AC and Botox groups averaged 0.702 and 0.707 QALYs, respectively. Estimates through 9 months favored Botox showing AC participants incurred higher cost per month of adequate symptoms control ($305) compared to Botox participants ($207). CONCLUSION: Botox and AC medications have similar costs and effectiveness in the first 6 months of UUI treatment. If costs and outcomes are considered through 9 months, Botox may have significantly lower costs but similar UUI symptom control as AC.